2022
DOI: 10.1088/1361-6498/ac87b8
|View full text |Cite
|
Sign up to set email alerts
|

Practical guidelines for personal monitoring and estimation of effective dose and dose to the lens of the eye in interventional procedures

Abstract: The estimation of the effective dose and the dose to the lens of the eye for workers involved in interventional workplaces is a complicated procedure. The practices that the interventional workers perform are related with high doses and, due to this, the workers need to wear protective garments. As a result, various methodologies have been developed to assess the effective dose and the dose to the lens of the eye. In the present study data, measurements from four European dosimetry services, over and under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…They also revealed that the dose level also varied from the work place like in Radio-pharmacy laboratory, dose level to extremities is 5 times more than the whole-body dose level and in cyclotron operation, the medial dose level to extremities is 100 times more than whole body median dose level which resulted that there is an underassessment of exposure level of radiation worker in medical applications. Askounis et al (2022) conducted an experiment in which various methods developed for the assessment of the effective dose and eye lens dose. Gbetchedji et al (2020) assessed the effective dose of occupational healthcare workers exposed in South Africa.…”
Section: Handling Of Radiopharmaceutical With Gm Probementioning
confidence: 99%
“…They also revealed that the dose level also varied from the work place like in Radio-pharmacy laboratory, dose level to extremities is 5 times more than the whole-body dose level and in cyclotron operation, the medial dose level to extremities is 100 times more than whole body median dose level which resulted that there is an underassessment of exposure level of radiation worker in medical applications. Askounis et al (2022) conducted an experiment in which various methods developed for the assessment of the effective dose and eye lens dose. Gbetchedji et al (2020) assessed the effective dose of occupational healthcare workers exposed in South Africa.…”
Section: Handling Of Radiopharmaceutical With Gm Probementioning
confidence: 99%